Three-dimensional flexible electrode derived from low-cost nickel–phytate with improved electrochemical performance. Issue 24 (1st June 2016) - Li, Panpan; Jin, Zhaoyu; Wang, Rui; Jin, Yong; Xiao, Dan
Abstract : A three-dimensional flexible electrode derived from nickel–phytate nanoplates was fabricated via a green approach, and showed outstanding performance in both water oxidation and supercapacitance. Abstract : We report a 3D flexible electrode, with a Cu nanowire array/polyimide membrane as the platform and nickel–phytate nanoplates as the electroactive material, used as an efficient water oxidation electrode and a favorable positive electrode for supercapacitors. The fabricated 3D electrode shows improved electrochemical performance, revealing the enhanced current density and ultra long-term electrochemical stability (7 days for electrocatalysis with 6% current density loss and 20 000 cycles for the galvanostatic charge–discharge measurements with 12% areal capacitance loss). With deep analysis, the crucial factors determining the great enhanced performance could be the outstanding electron transfer provided by the 3D-nanowires support, the large electrochemically active surface area (EASA) and the formation of NiO x species with a high oxidation state. Moreover, the growth mechanism of the Ni–phytate compounds is carefully investigated. Importantly, this green approach considered to be a corrosion-growth process is conducted under mild conditions and involves the application of phytic acid, abundant in living organisms, could have potential in future research.